The economics book big ideas simply explained - Kishtainy, Niall (London Dorling Kindersley, 2012)
"Reveals the many ideas and schools of economics that have emerged since trading first began in ancient times."--Front jacket flap.
Let the trading begin: 400 BCE-1770 CE -- The age of reason: 1770-1820 -- Industrial and economic revolutions: 1820-1929 -- War and depressions: 1929-1945 -- Post-war economics: 1945-70 -- Contemporary economics: 1970-present.
Keywords: Economics; Economics -- Methodology; Economics -- History; Economists